Bibliometric Analysis: Research Trends on Deliberative Models in Learning Approaches in the Digital Era - Muhkam, Mirwan Fikri; Rahmat; Abdulkarim, Aim; Komalasari, Kokom (Journal of Pedagogy and Education Science, 2025)
This study aims to examine the development and trends of research related to deliberative models in learning approaches in the digital era. Research data were obtained using the Publish or Perish 8 application by taking references from journals indexed by Google Scholar. A total of 1000 articles relevant to the keywords "deliberative model" AND "digital era" from 2018 to 2025 were successfully collected. The data was then analyzed and visualized using the VOSviewer application. The results provide insight into the development of deliberative model research in the digital technology era. Bibliometric analysis reveals research trends from year to year, the main contribution of the number of citations, and the development of key concepts in the literature. The results of this study can provide a foundation for future research to understand better the deliberative model in the education approach in the digital technology era.